Primary Ion Depletion Kinetics (PIDK) Studies as a New Tool for Investigating Chemical Ionization Fragmentation Reactions with PTR-MS - Schuhfried, Erna (Public Library of Science, 2013)
We report on a new approach for studying fragmentation channels in Proton Transfer Reaction-Mass Spectrometry (PTR-MS), which we name primary ion depletion kinetics (PIDK). PTR-MS is a chemical ionization mass spectrometric (CIMS) technique deploying hydronium ions for the chemical ionization. Induced by extremely high concentrations of analyte M, depletion of the primary ions in the drift tube occurs. This is observed as quasi zero concentration of the primary ion H(3)O(+), and constant MH(+). Under these non-standard conditions, we find an overall changed fragmentation. We offer two explanations. Either the changed fragmentation pattern is the result of secondary proton transfer reactions. Or, alternatively, the fast depletion of H(3)O(+) leads to reduced heating of H(3)O(+) in the drift field, and consequently changed fragmentation following protonation of the analyte M. In any case, we use the observed changes in fragmentation as a successful new approach to fragmentation studies, and term it primary ion depletion kinetics, PIDK. PIDK easily yields an abundance of continuous data points with little deviation, because they are obtained in one experimental run, even for low abundant fragments. This is an advantage over traditional internal kinetic energy variation studies (electric field per number density (E/N) variation studies). Also, some interpretation on the underlying fragmentation reaction mechanisms can be gleamed. We measure low occurring fragmentation (<2% of MH(+)) of the compounds dimethyl sulfide, DMS, a compound that reportedly does not fragment, diethyl sulfide DES, and dipropyl sulfide DPS. And we confirm and complement the results with traditional E/N studies. Summing up, the new approach of primary ion depletion kinetics allows for the identification of dehydrogenation [MH(+) -H(2)] and adduct formation (RMH(+)) as low abundant fragmentation channels in monosulfides.